Pujian Kenabian (Madh al-Nabawiy) dalam Puisi ‘Issa Jarȃba di Twitter (Kajian Struktural Puisi Arab) - Sammad Hasibuan (Universitas Al Azhar Indonesia, 2022)
Abstract - In addition to using beautiful stylistic elements, the theme of praise is also an element that enhances the structure of Arabic poetry. ‘Issa Jarȃba is one of the contemporary Arab writers who is working in the Digital World. He often shares his works in the form of poetry on Twitter. One of the most interesting aspects of his poems is their theme. Therefore, this study aims to describe the themes that are often expressed in the 20 titles of poetry that he uploads through his personal Twitter account. In this study, the researcher used descriptive analytical method, while the theory used was structural theory. However, the structural element that is emphasized in this research is the theme element. The results show that the theme that is often raised by 'Issa Jarȃba in his poetry is the theme of praise to the Prophet Muhammad SAW, including praise of the superiority of the Prophet Muhammad over other prophets and praise of the perfect characteristics of the Prophet Muhammad. In addition, some of his poetry works are typographicalized by Qasdah and some are in the form of Modern poetry. The research is expected to add to the scientific treasures of cyber literature. Keywords - Prophetic Praise; 'Issa Jarba; Twitter; Arabic poetry; CyberLiterature